QoS Parameters for Viable SLA in Cloud - Raza, Muhammad Raheel; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2020)
Quality of Service (QoS) is a key factor for a viable Service Level Agreement (SLA) which ensures the formation of a reliable provider-consumer relationship in cloud computing. SLA ties up a service provider with a service consumer on agreed upon terms and conditions so that the provider's promised services and the consumer's requirements are fulfilled which results in a trustful relationship between them. In this paper, an analysis of the existing literature is made to identify the gaps needed to be filled for establishing a trustful relationship. The literature is classified w.r.t the QoS potential attributes i.e. trust, resource management, risk management, security, task scheduling and performance etc. contributing to maintain a feasible SLA. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: cloud; cloud computing; performance; QoS; resource allocation; risk management; security; SLA; task scheduling; trusted relationship